2016
DOI: 10.1007/s10620-016-4118-1
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenterologists Have Suboptimal Hepatitis B Virus Screening Rates in Patients Receiving Immunosuppressive Therapy

Abstract: HBV screening prior to immunosuppressive therapy is suboptimal, especially among gastroenterologists. Efforts to improve screening rates in at risk populations are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
(36 reference statements)
2
21
0
Order By: Relevance
“…[2123,29] Studies looking at a broader range of immunosuppressants reported HBV screening rates of 6% to 62%, with wide variations according to ordering clinic. [3034] As described in other settings, we also found patients seen by nephrologists and kidney transplant patients to have the highest probability of adequate screening. [30] …”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…[2123,29] Studies looking at a broader range of immunosuppressants reported HBV screening rates of 6% to 62%, with wide variations according to ordering clinic. [3034] As described in other settings, we also found patients seen by nephrologists and kidney transplant patients to have the highest probability of adequate screening. [30] …”
Section: Discussionsupporting
confidence: 66%
“…[3034] As described in other settings, we also found patients seen by nephrologists and kidney transplant patients to have the highest probability of adequate screening. [30] …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…21,22 In our current study, although overall HBV screening rates were suboptimal, HBV screening before RTX improved nearly 5-fold over the span of the study. Studies among patients who receive RTX also demonstrate suboptimal HBV screening rates.…”
Section: Discussionmentioning
confidence: 62%
“…At the author's institution, a retrospective review of 4008 patients who had received immunosuppressive therapy for both malignant and non-malignant disease showed only 46.7 % of patients screened prior to initiating treatment [80]. Among patients receiving rituximab, only 48.3 % patients were screened, compared to 35.7 % who received nonrituximab-containing treatment.…”
Section: Screeningmentioning
confidence: 99%